Innovation in Aqidah Akhlak Learning: Implementing Think Pair Share to Cultivate Religious Moderation Values - Azar, Dhea; Pahrudin, Agus; Hasanah, Ida Faridatul; Irawan, Rudy; Fitriani, Fitriani; Susanti, Agus (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The rapid pace of globalization and digital technology, coupled with the inherent social diversity in Indonesia, increases the risk of social conflict and intolerance. In this context, conventional teaching methods in religious education often fail to deeply instill the values of religious moderation needed to navigate such a complex environment. This study will investigate and describe the development of the Think Pair Share (TPS) instructional model as a strategic tool for cultivating religious moderation values among students within the subject of Faith and Moral Education (Akidah Akhlak). A descriptive qualitative approach was employed at State Islamic High School (MAN) 1 Bandar Lampung. Data were gathered through in-depth interviews with teachers of Faith and Moral studies and students, followed by thematic analysis to understand the implementation and impact of the learning model. The findings indicate that the implementation of the TPS model yields significant positive outcomes. The "Think" phase allows for individual reflection, the "Pair" phase fosters collaborative dialogue, and the "Share" phase encourages respect for diverse viewpoints. This process helps students not only understand theoretical ideas but also learn and practice the basic ideas of religious moderation, like tolerance (tasamuh), balance (tawazun), and non-violence. The model creates an interactive space where students refine their communication skills and develop an appreciation for differing perspectives. This study provides a paradigm for character building and active learning in Islamic education. It offers educators a reproducible technique to shift religious education from theoretical instruction to a transforming experience that fosters social harmony and moderate religious identification.